2018
DOI: 10.7573/dic.212561
|View full text |Cite
|
Sign up to set email alerts
|

Severe refractory asthma: current treatment options and ongoing research

Abstract: Patients with severe asthma have a greater risk of asthma-related symptoms, morbidities, and exacerbations. Moreover, healthcare costs of patients with severe refractory asthma are at least 80% higher than those with stable asthma, mainly because of a higher use of healthcare resources and chronic side effects of oral corticosteroids (OCS). The advent of new promising biologicals provides a unique therapeutic option that could achieve asthma control without OCS. However, the increasing number of available mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 111 publications
(117 reference statements)
0
21
1
Order By: Relevance
“… 12 In fact, those who had experience with anti-IL5 therapy did not think that any of the anti-IL5 medications were superior to the others, but they preferred a more precision-based approach for each patient. 27 , 28 More interestingly, doctors with previous anti-IL5 experience did not believe that switching to another anti-IL5 following an incomplete response to anti-IL5 treatment would be beneficial, despite some conflicting evidence. 15 Those with previous anti-IL5 experience were confident that anti-IL5 drugs can be beneficial in concomitant nasal polyposis and, in fact, a recent review concluded that omalizumab, mepolizumab, and reslizumab are effective in improving nasal polyposis.…”
Section: Discussionmentioning
confidence: 99%
“… 12 In fact, those who had experience with anti-IL5 therapy did not think that any of the anti-IL5 medications were superior to the others, but they preferred a more precision-based approach for each patient. 27 , 28 More interestingly, doctors with previous anti-IL5 experience did not believe that switching to another anti-IL5 following an incomplete response to anti-IL5 treatment would be beneficial, despite some conflicting evidence. 15 Those with previous anti-IL5 experience were confident that anti-IL5 drugs can be beneficial in concomitant nasal polyposis and, in fact, a recent review concluded that omalizumab, mepolizumab, and reslizumab are effective in improving nasal polyposis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even in patients with fixed airflow obstruction and obesity, a significant improvement of lung function has been observed during benralizumab treatment course 38. Benralizumab also demonstrated a greater steroid-sparing effect in comparison with other anti IL-5 drugs 4…”
Section: Target Population: Potential Predictors Of Efficacymentioning
confidence: 93%
“…Eosinophilic asthma is a relevant subtype of asthma associated with increased risk of severe exacerbations and a difficult control, despite high doses of oral and inhaled corticosteroids. In the last decades, that asthma phenotype has been extensively explored, and the increasing evidence concerning the underlying inflammation mechanisms has highlighted new potential therapeutic targets and subsequently has paved the way to new selective drugs 4. In the next few years further biologic and bio-similar molecules selectively addressing eosinophils and Th2 inflammation will become available on the market, substantially enlarging the treatment options for the patients with severe eosinophilic asthma 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Omalizumab, a monoclonal antibody (mAb) that specifically targets IgE, was the first mAb approved for the treatment of severe asthma, in a specific subpopulation of patients with uncontrolled IgE-mediated allergic asthma. Recently, new options, such as anti-IL-5 mAbs and anti-IL-4/IL-13, are available or will be in the near future 11. Asthma is increasingly recognized as a syndrome with similar clinical presentations rather than a single disease.…”
Section: Introductionmentioning
confidence: 99%